Abrasion and skid resistance of concrete containing waste polypropylene fibers and palm oil fuel ash as pavement material. (3rd May 2021) - Alaskar, Abdulaziz; Alabduljabbar, Hisham; Mustafa Mohamed, Abdeliazim; Alrshoudi, Fahed; Alyousef, Rayed
Highlights: Concrete mixtures were reinforced with waste PP fibers. The abrasion and skid resistance tests were carried out. The abrasion and skid resistance enhanced with an increase in PP fiber dosages. Concrete mixtures containing PP fiber are potential to be used as pavement materials. Abstract: During the entire service life of pavement, the exposed surface must have an adequate level of roughness, so as to expedite the friction amongst vehicle wheels and the surface of the pavement. Therefore, the abrasion and skid resistance should be considered when measuring the wear, sliding, and skidding levels of a pavement surface. It is well-known that the lower the skid resistance value, the higher the percentage of traffic accidents (particularly under wet conditions). Therefore, this study aimed to enhance the abrasion and skid resistance of concrete as a pavement material by reinforcement with polypropylene (PP) fibers. The influences of waste PP fibers and palm oil fuel ash (POFA) on the tensile and compressive strengths, modulus of elasticity, abrasion resistance (tested using a Bohme surface abrasion machine), and skid resistance (tested using a British pendulum skid resistance tester) of the concrete were investigated. Overall, 12 mixes were cast, including six concrete mixtures comprising 0%, 0.25%, 0.5%, 0.75%, 1%, and 1.25% PP fibers with 100% ordinary Portland cement (OPC). Another six concrete mixtures were prepared with the same fiber dosages, but with 20% POFA as a cement replacement. The experimental results revealed that using PP fibers at concentrations up to 1.25% reduced the compressive strength of concrete mixtures by approximately 17%. However, the addition of PP fibers significantly enhanced the tensile strength (by 30%), along with the abrasion and skid resistance of all of the fiber-reinforced concrete mixtures. It was found that the 1.25% PP fiber mix had the highest abrasion and skid resistance, i.e., approximately 25% higher than that of a control mix. In addition, the POFA mixes performed better than the OPC mixes, owing to the high pozzolanic activity and the formation of additional hydration products.